B.P. Hasdeu and the Possibility of Founding Phraseology as a Science - Munteanu, Cristinel (Acta Universitatis Danubius. Communicatio, 2024)
In a concise study from 1882, B.P. Hasdeu presented his own classification of the linguistic sciences (seen as subdivisions of glottics, i.e., the science of language) and justified the distinctions made according to mainly formal and semantic criteria. At the same time, Hasdeu also took into consideration two physical-psychical aspects of linguistic units, namely their “fluid” and “condensed” features. As a result of combining these criteria and aspects, a series of sub-sciences were individualized (whether their object was either the word or the sentence). I aimed at demonstrating that the respective criteria also allow the individualization of phraseology (or the delimitation of its object). However, it seems that the time of phraseology had not come yet, since Hasdeu left a “blank space” in his classification – the very place of phraseology.